A CASE STUDY OF CHATGPT-INTEGRATED GENRE-BASED INSTRUCTION FOR EFL NARRATIVE WRITING DEVELOPMENT - Ahmad Syairofi (Indonesian EFL Journal, 2026)
Although the use of a genre-based approach in teaching writing has been extensively researched, little is known about how AI technology is incorporated into such an approach to assist Indonesian EFL students in developing their writing skills. To fill this gap, this study investigates the incorporation of AI technology (i.e., ChatGPT) within a genre-based instructional framework to identify areas of improvement in students’ writing following the implementation of the teaching program. Informed with AI literacy, the instructional design is enacted iteratively to teach narrative texts. Data from this case study were collected from students’ writings (diagnostic test and after-teaching test) and semi-structured interviews. The students’ artefacts (n=16 for each diagnostic test and after-teaching test) were analyzed using Systemic Functional Linguistics, while students’ interviews were discursively read and analyzed thematically to support the previous data. The findings suggest positive developmental changes compared to their scores on the diagnostic test. Additionally, the semi-structured interviews revealed that most students had a positive experience, reporting that they felt well-prepared to write narrative texts using the model. Developments were noted in language use and text structure, with students being actively engaged and receiving direct feedback from peers, the tool, and the teacher. The study concludes with implications and recommendations for future research.